How Much Hypertension is Attributed to Overweight, Obesity, and Hyperglycemia Using Adjusted Population Attributable Risk in Adults? - Ebrahim Babaee; Arash Tehrani‐Banihashem; Babak Eshrati; Majid Purabdollah; Marzieh Nojomi (International Journal of Hypertension)
Background. High blood pressure (HBP) is a proven risk factor for cardiovascular diseases. So, determining the extent of the contribution of the factors associated with HBP seems to be necessary. Accordingly, this study aimed to investigate how much the prevalence of HBP attributed to obesity and high blood glucose (HBG). Methods. Data were collected from 7612 participants extracted from a screening program in 2018, in Iran, which was conducted on the subjects with the age of 30 years old and older to investigate the prevalence of HBP and their associated risk factors. To collect data, we used a standard checklist in terms of the WHO STEPS manual, and a stratified multistage sampling method was also applied. The adjusted population attributable risk of overweight, obesity, and HBG for HBP was calculated by the logistic regression model using the aflogit module. Results. Among the studied people, 7.4% of male and 10.8% of female subjects were hypertensive. The adjusted analysis showed that, in men, 27% and 41% and, among women, 19% and 37% of HBP prevalence rates were attributable to obesity (BMI ≥ 30) and fast blood sugar (FBS) (≥126), respectively. In people with both obesity and HBG, 59% of the prevalence rate of HBP in men and 46% of the prevalence in women were due to the abovementioned risk factors altogether. The results show that, if obesity and HBG were eliminated, the prevalence of HBP could be theoretically decreased from 7.4% to 5.4% and 4.3% in male subjects and from 10.8% to 8.7% and 6.8% in female subjects, respectively. Conclusions. Our findings indicate that how much the prevalence of HBP attributes to obesity and HBG in middle-age and older population. It seems that the prevention programs should be administered in the general population, and excess body weight prevention programs should also be implemented in childhood.